Providing Intradialytic Parenteral Nutrition Therapy Does Not Improve Anthropometric Status in Hemodialysis Patients with Malnutrition - Suryantoro, Satriyo Dwi; Tjempakasari, Artaria; Nurwidda, Arvi Dian Prasetia; Widodo, Widodo; Thaha, Mochammad; Mardiana, Nunuk (PERNEFRI (PERHIMPUNAN NEFROLOGI INDONESIA), 2024)
Background: Malnutrition is prevalent in hemodialysis patients and significantly impacts prognosis. It can result from reduced food intake and protein loss during hemodialysis. Nutritional status is determined through anthropometric examinations, which include upper arm circumference (UAC), body mass index (BMI), hand grip strength, bicep, and tricep fold thickness. Laboratory examinations like total cholesterol and Malnutrition Inflammation Score (MIS) or Subjective Global Assessment (SGA) are also used. Intradialytic Parenteral Nutrition (IDPN) is expected to maintain or improve the nutritional status of hemodialysis patients. Objective: This research examines the impact of parenteral nutrition therapy on the anthropometric status of malnourished hemodialysis patients. Methods: This cross-sectional study, a sub-analysis of a larger nutritional therapy study, involved 24 hemodialysis patients experiencing malnutrition based on SGA B and C criteria with 1-10 years of hemodialysis. IDPN therapy was provided, and anthropometric measurements and total cholesterol were taken at baseline and three months after nutritional therapy. Data processing used comparative statistical analysis. Results: The mean age was 45.33 years, with 14 males and 10 females. After 3 months, there were no significant differences in UAC (mean difference = 0.13; p = 0.69), BMI (mean difference = 0.13; p = 0.50), hand grip strength (mean difference = -0.96; p = 0.282), biceps skinfold thickness (mean difference = 0.13; p = 0.69) and triceps (mean difference = 0.59; p = 0.134) or total cholesterol (mean difference = -1.5; p = 0.71). Conclusion: IDPN therapy for 3 months did not improve the anthropometric status of hemodialysis patients with malnutrition.